2011
DOI: 10.1007/s10549-011-1931-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary angiosarcomas of the breast: a single institution experience

Abstract: Angiosarcomas of the breast (ASB) are rare, representing <1% of breast malignancies. They can develop as a primary or secondary malignancy, also called post-radiation angiosarcoma. The aim of the this study is to discuss diagnosis, treatment, and outcome of primary and secondary ASB patients, diagnosed and treated in a single institution, over a 10-year period and to further compare the two conditions. We retrieved 28 consecutive cases of ASB, diagnosed from 1999 to 2009 at the European Institute of Oncology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 36 publications
2
38
1
Order By: Relevance
“…Our findings confirm the fact that secondary tumors have a worse prognosis when compared with primary disease, as we previously reported in a series addressing a smaller number of cases [3,26]. We also found a significant association between MYC amplification and poor prognosis in secondary angiosarcomas of the breast.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings confirm the fact that secondary tumors have a worse prognosis when compared with primary disease, as we previously reported in a series addressing a smaller number of cases [3,26]. We also found a significant association between MYC amplification and poor prognosis in secondary angiosarcomas of the breast.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with secondary AS presented with skin changes (rash and ecchymosis) with concomitant ulceration and/or bruising. Clinicopathological features from 28 cases of AS included in the present series were previously described [3]. Thirty patients were diagnosed with post-radiation AVL of the breast (Fig.…”
Section: Clinicopathological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the findings of previous reports , a high rate of local recurrence (45%) rather than distant metastasis (30%) was observed in our series. Local recurrences and metastases from hematogenous dissemination were relatively common.…”
Section: Discussionsupporting
confidence: 93%
“…It often presents following radiotherapy for breast cancer, usually after an interval of several years [2]. Primary de novo angiosarcoma of the breast is rare [3] and usually seen in relatively young women in the child bearing age group [4]. Up to half of angiosarcomas are associated with metastatic disease, either at presentation or developing subsequently [5], and several case series have shown that these tumors most often metastasize to the liver, lung, or bones [6, 7].…”
Section: Introductionmentioning
confidence: 99%